Media in Perú and the global trend: regarding the essay on the civilization of entertainment - González Fuentes, Cecilia Gabriela (2014)
This article shows the main ideas of the Peruvian-Spanish wríter Mario Vargas Llosa on the phenomenon of how traditional culture is being displaced by mass culture and entertainment. Based on such analysis, the article examines the contents of the Peruvian media, presenting specific cases showing sorne form of violen ce víolating the fundamental ríghts of individuals; while descríbing the way such cases are treated at local and international levels. Then, the author propases a reflection on the impact of the violence portrayed in entertainment and on the need to promote qualitative changes allowing for the gradual adaptation of the media to the social purposes it is expected to pursue in light of the Constitution and laws. It also identifies existing regulatory and oversight mechanisms, considering them opportunities for ordinary citizens to participate in the change that reality demands.